2011
DOI: 10.3233/thc-2011-0613
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative three-dimensional imaging in tibial plateau fractures with complex depressions

Abstract: Introduction: The aim of the study was to investigate the role of the intra-operative three-dimensional imaging in the tibial plateau fractures with complex depressions.Material and methods: Thirty tibial plateau fracture patients with complex depression were treated with the use of intraoperative three-dimensional imaging (Arcadis 3D). The image quality as well as the clinical benefit was evaluated.Results: In total 74 plates were used in these 30 patients. Six Kirschner wires and 50 screws were used outside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…One reason for this was that tibial plateau fractures were viewed as a subgroup. Ruan et al and Kendoff et al obtained similar results for the revision rate (20% and 21%, respectively) as observed in this study [11, 13].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One reason for this was that tibial plateau fractures were viewed as a subgroup. Ruan et al and Kendoff et al obtained similar results for the revision rate (20% and 21%, respectively) as observed in this study [11, 13].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, relatively small numbers of fractures were investigated; in some studies, proximal tibia fracture was only analyzed as a subgroup. These publications report a revision rate from 11 to 21% based on 3D imaging [1013].…”
Section: Introductionmentioning
confidence: 99%
“…They also detected relevant intraarticular fragments, which would have remained undetected in conventional fluoroscopy [28]. Also, other authors have confirmed the benefit of intraoperative 3D imaging [29,30]. Synoptically, in general the intraoperative 3D scan offers an advantage over conventional imaging.…”
Section: Intraoperative 3d-imagingmentioning
confidence: 83%
“…1 . There were seven prospective cohort studies [ 20 , 21 , 24 , 27 , 28 , 32 , 34 ], four retrospective cohort studies [ 16 , 19 , 26 , 29 ], five case series [ 22 , 23 , 30 , 31 , 33 ], two case reports [ 17 , 18 ], one descriptive study [ 8 ], and one observational study [ 25 ]. No Randomized controlled trials were found.…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, 22 articles were included for full-text screening of which two articles were excluded [14,15]. Twenty studies met the inclusion criteria of this systematic review [8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The review process is summarized in Fig.…”
Section: Searchmentioning
confidence: 99%